Islamic Republic of Afghanistan : Technical Assistance Report-Report on Government Finance Statistics Technical Assistance Mission (October 18-31, 2018). (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper assesses Islamic Republic of Afghanistan government's finance statistics (GFS). The mission updated the AFMIS bridge tables to enable producing Budgetary Central Government data according to the GFSM 2014 classifications including the economic (object) and functional classifications, reviewed government debt compilation, assisted developing bridge tables for extrabudgetary units, and provided hands-on training for GFS compilers in compiling the data for the general government. Despite good outcomes, the capacity for GFS compilation remains slim and securing support of the management remains critical for both maintaining the current achievements and further improving the government financial data consistent with the GFSM 2014 methodology. Afghanistan has made good steps toward further improving GFS and starting to provide supplementary accrual information, while there have been issues with the quality of the source data. The mission suggests that a GFS Technical Working Group should be set up to coordinate the GFS reforms, address the issues in applying the GFSM 2014 methodology, and advise the Ministry of Finance management on important matters requiring attention.